Divert when it does not hurt: The initiation of economic sanctions by US presidents from 1989 to 2015 - Hana Attia (Review of International Economics, 2023)
A dominant argument in the literature is that leaders tend to initiate military disputes in periods plagued by economic distress. This article revisits the diversionary theory and adapts it to the use of economic sanctions in the United States, contending that their use follows a similar diversionary logic. Using a novel dataset on US sanctions from 1989 to 2015, I find that presidents are more likely to use sanctions when unemployment is high and the president's party power in Congress is weak. I show that when doing so presidents opt for sanctions that inflict little harm on the US economy.
Keywords: 330; diversion; economic coercion; sanctions; US politics